Noise-induced hearing loss is correlated with alterations in the expression of GABAB receptors and PKC gamma in the murine cochlear nucleus complex - Kou, Zhen-Zhen; Qu, Juan; Li, Hui; Zhang, Dong-Liang; Li, Yun-Qing (Frontiers in Neuroanatomy, 2013)
Noise overexposure may induce permanent noise-induced hearing loss (NIHL). The cochlear nucleus complex (CNC) is the entry point for sensory information in the central auditory system. Impairments in gamma-aminobutyric acid (GABA) - mediated synaptic transmission in the CNC have been implicated in the pathogenesis of auditory disorders. However, the role of protein kinase C (PKC) signaling pathway in GABAergic inhibition in the CNC in NIHL remains elusive. Thus, we investigated the alterations of glutamic acid decarboxylase 67 (GAD67, the chemical marker for GABA-containing neurons), PKCsubunit (PKC) and GABAB receptor (GABABR) expression in the CNC using transgenic GAD67-green fluorescent protein (GFP) knock-in mice, BALB/c mice and C57 mice. Immunohistochemical results indicate that the GFP-labeled GABAergic neurons were distributed in the molecular layer (ML) and fusiform cell layer (FCL) of the dorsal cochlear nucleus (DCN). We found that 69.91% of the GFP-positive neurons in the DCN were immunopositive for both PKC and GABABR1. The GAD67-positive terminals made contacts with PKC/GABABR1 colocalized neurons. Then we measured the changes of auditory thresholds in mice after noise exposure for 2 weeks, and detected the GAD67, PKC and GABABR expression at mRNA and protein levels in the CNC. With noise over-exposure, there was a reduction in GABABR accompanied by an increase in PKCexpression, but no significant change in GAD67 expression. In summary, our results demonstrate that alterations in the expression of PKCand GABABRs may be involved in impairments in GABAergic inhibition within the CNC and the development of NIHL.